Single giant mediastinal rhabdomyoma as a sole manifestation of TSC in foetus - Godava, Marek; Filipova, Hana; Dubrava, Lubomir; Vrtel, Radek; Michalkova, Kamila; Janikova, Maria; Bakaj-Zbrozkova, Lenka; Navratil, Jiri (Biomedical papers, 2017)
Background: Presence of multiple cardiac rhabdomyomas is one of the major features of Tuberous sclerosis (TSC), but isolated progressing single giant rhabdomyoma is very rare and not typical of TSC. Case report: This report presents family without obvious history of TSC with occurrence of giant mediastinal rhabdomyoma affecting the haemodynamics in male foetus, without other TSC symptoms. Girl from the next gravidity had prenatally detected multiple rhabdomyomas and small subcortical tuber of brain detected after birth. DNA analysis found novel c.4861A>T TSC2 variant and large deletion in TSC2 in tumour tissue from male foetus. The novel TSC2 variant was also present in the girl and her healthy father, in silico analysis suggested its functional effect on TSC2. Brain MRI of the father detected mild TSC specific abnormality. Conclusion: We suggest the novel TSC2 mutation is a cause of mild TSC in this family and has reduced expression. The clinical and molecular findings in this family also emphasize that TSC diagnosis should be also evaluated in case of single giant foetal cardiac rhabdomyoma.
Keywords: cardiac rhabdomyoma; TSC2; reduced expression; mild tuberous sclerosis.